The Effect of Audit Fee, Audit Tenure, Company Size, Audit Rotation, and Institutional Ownership on Audit Quality (Empirical Study on Property and Real Estate Companies Listed on the Indonesia Stock Exchange in 2018-2020) - Qoonita Afiifah Adzroo; Lintang Kurniawati (Prosiding University Research Colloquium, 2022)
This study aims to determine the effect of audit fees, audit tenure, size of company, audit rotation, and institutional ownership of audit quality in companies listed on the Indonesia Stock Exchange (IDX). Dependent variable used in this study is audit quality and the independent variables in this study are audit fees, audit tenure, company size, audit rotation and institutional ownership. The population in this study are property and real estate companies registered in Indonesia Stock Exchange 2018-2020. Samples were taken by purposive sampling method and obtained 37 companies as samples. The hypothesis testing of this research was carried out by using linear regression analysis. The result of this study indicates that the fee audit, audit tenure, audit rotation and institusional ownership have no effect on audit quality, while company size has an effect on audit quality.